2012
DOI: 10.1097/nen.0b013e3182588293
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomic Connectivity of the Human Ascending Arousal System Critical to Consciousness and Its Disorders

Abstract: The ascending reticular activating system (ARAS) mediates arousal, an essential component of human consciousness. Lesions of the ARAS cause coma, the most severe disorder of consciousness. Because of current methodological limitations, including of postmortem tissue analysis, the neuroanatomic connectivity of the human ARAS is poorly understood. We applied the advanced imaging technique of high angular resolution diffusion imaging (HARDI) to elucidate the structural connectivity of the ARAS in 3 adult human br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
413
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(454 citation statements)
references
References 76 publications
9
413
0
12
Order By: Relevance
“…8,[37][38][39][40][41] Since the introduction of DTI, several studies have reported on the lower portion of the ARAS in healthy subjects and patients with brain injury. 5,6,12,13 In 2012, Edlow et al 6 reconstructed the ARAS connecting the brain stem to the thalamus, hypothalamus, and the basal forebrain in healthy subjects. In 2013, Yeo et al 5 reported a method for reconstruction of the lower portion of the ARAS from the pontine reticular formation to the thalamus in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,[37][38][39][40][41] Since the introduction of DTI, several studies have reported on the lower portion of the ARAS in healthy subjects and patients with brain injury. 5,6,12,13 In 2012, Edlow et al 6 reconstructed the ARAS connecting the brain stem to the thalamus, hypothalamus, and the basal forebrain in healthy subjects. In 2013, Yeo et al 5 reported a method for reconstruction of the lower portion of the ARAS from the pontine reticular formation to the thalamus in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] By contrast, diffusion tensor tractography, which is derived from diffusion tensor imaging, has enabled 3D reconstruction and estima-tion of the ARAS in the healthy human brain. 5,6 In addition, a few studies have reported injury of the ARAS in patients with traumatic brain injury and hypoxic-ischemic brain injury by using diffusion tensor tractography. 12,13 However, no study on injury of the ARAS in patients with SAH has been reported, to our knowledge.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We first assessed whether structural injury to the pons, midbrain, and thalamus accounted for unresponsiveness in our population, as these structures are known to be critical for arousal. 27,28 Second, we used resting-state fMRI to identify from a screen of multiple standard networks those that were disrupted in unresponsive patients. We then directly interrogated the DMN and its relationship to TPN in our study group.…”
Section: Strokementioning
confidence: 99%